Repercussions of COVID-19 on the morbidity and mortality of indigenous children: integrative review - Siqueira, Francielle Brum dos Santos de; Figueiredo, Camila Lovato de; Fortes, Gleicimara Raquel; Ribeiro, Aline Cammarano; Siqueira, Fernanda Duarte; Neves, Eliane Tatsch (O Mundo da Saúde, 2024)
The disease caused by COVID-19 had an impact on the health of indigenous communities, with hospitalization and death rates, mainly in the children’s segment. The objective of the study was to identify scientific evidence about the repercussions of COVID-19 on the morbidity and mortality of indigenous children. This is an integrative review study with the research question: What are the repercussions of the COVID-19 pandemic on indigenous children? The PUBMED, WEB OF SCIENCE, LILACS and SCOPUS data sources were accessed during the month of December 2023 with the search strategies: “indigenous population” AND “child” AND “coronavirus infections” and “native” AND “child” AND “coronavirus infections”, taking 2020 as the epidemiological milestone. Based on the inclusion criteria, nine scientific productions were selected. After interpreting the results, it was identified that indigenous children have a higher risk of mortality compared to non-indigenous children of the same age. This may be related to increased vulnerability, difficulty accessing food and prematurity. It was concluded that indigenous children had higher mortality rates and other implications related to COVID-19 and repercussions related to existing social inequalities and vulnerabilities that increased with the pandemic. The scarce scientific production regarding the indigenous population stands out, especially with regard to children.